2022
DOI: 10.16953/deusosbil.1191833
|View full text |Cite
|
Sign up to set email alerts
|

Authenticity Perception Customer Satisfaction, Destination the Effect of Image on Behavioral Intention: The Example of Izmi̇r the Historical City of Birgi

Abstract: Bu çalışmanın amacı, otantiklik algısı, müşteri tatmini ve destinasyon imajının davranışsal niyete etkisinin incelenmesidir. Araştırmanın evrenini İzmir ilinin Birgi tarihi kentini ziyaret eden turistler oluşturmaktadır. Araştırmada 02 Haziran-25 Eylül 2022 tarihleri arasında amaçlı örnekleme yöntemlerinden ölçüt örneklemesi ile 401 anket toplanmıştır. Araştırmada hipotezlerin test edilmesi için Smart PLS 4 istatistik programı kullanılmış olup, verilerin çözümlenmesinde yapısal eşitlik modelinden faydalanılmış… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 104 publications
(65 reference statements)
0
0
0
Order By: Relevance
“…Demographic questions were included to determine the demographic profiles of tourists. It was clear that exemplary destination image studies in Turkey were conducted in Trabzon (Yaraşlı, 2007), Diyarbakır (Dinç, 2020), and İzmir (Baydeniz et al, 2022). Hence, it is observed that the validity and reliability of the questions in the research have been tested before and are suitable for related research.…”
Section: Methodsmentioning
confidence: 99%
“…Demographic questions were included to determine the demographic profiles of tourists. It was clear that exemplary destination image studies in Turkey were conducted in Trabzon (Yaraşlı, 2007), Diyarbakır (Dinç, 2020), and İzmir (Baydeniz et al, 2022). Hence, it is observed that the validity and reliability of the questions in the research have been tested before and are suitable for related research.…”
Section: Methodsmentioning
confidence: 99%